Psychological impact of the Sars-Cov-2 pandemic in university students: A Systematic Review - Sílvia Maria Fernandes Ala; Francisco Ramos Campos; Inês Carvalho Relva (Motricidade)
The objective of this research is to point out studies that describe variables that are associated with the impact of contingency measures resulting from the pandemic on the mental health of university students. A systematic review was carried out, following the PRISMA-P guidelines and PECO approach, the review protocol was registered in INPLASTY. The search was carried out in five databases, from December 2019 to December 2022. A selection process was carried out by title, abstract and full text, according to the inclusion and exclusion criteria. Initially, 27,458 articles were identified, and after eliminating duplicates, applying the inclusion criteria and critical analysis, 11 original articles were selected for qualitative analysis. The sample size was 47,552 participants, the majority of whom were women (68.07%) with an average age of 21.07 years. It was concluded that contingency measures (social isolation, quarantine, distancing) as a measure to prevent the spread of the pandemic had a negative impact on the psychological well-being of university students. Adequate support and research into which interventions can mitigate these risks are essential. We suggest the implementation of psychological interventions, which should be promoted proactively, to minimize negative impacts.